Additions to the taxonomy of Gnamptogenys Roger (Hymenoptera: Formicidae: Ectatomminae) with an updated key to the New World species - Camacho, Gabriela P.; Franco, Weslly; Feitosa, Rodrigo M. (Zootaxa, 2020)
This study aimed to raise and address nomenclatural issues surrounding Neotropical species in the genus Gnamptogenys, in addition to describing new species accumulated in myrmecological collections. New and reinstated names recognized here include G. pernambucana (Santschi) sp. rev., stat.n., G. lenis sp. n., G. latistriata sp. n., and G. avus sp. n. The queen and intercaste of G. lavra Lattke and the queen of G. pernambucana are described for the first time. For these five species we provide complete descriptions and diagnoses, comments on taxonomy and natural history, distribution data, and high-resolution images, including the first images of G. lavra. An updated identification key for all the Neotropical species of Gnamptogenys is also provided, including the new and revived species as well as G. aspera Morgan and G. pilosa Lattke, not present in previous keys for the genus.